Enhancement of glossiness perception by retinal-image motion: additional effect of head-yoked motion parallax. - Yusuke Tani (Public Library of Science (PLoS), 2013)
It has been argued that when an observer moves, a contingent retinal-image motion of a stimulus would strengthen the perceived glossiness. This would be attributed to the veridical perception of three-dimensional structure by motion parallax. However, it has not been investigated whether the effect of motion parallax is more than that of retinal-image motion of the stimulus. Using a magnitude estimation method, we examine in this paper whether cross-modal coordination of the stimulus change and the observer's motion (i.e., motion parallax) is essential or the retinal-image motion alone is sufficient for enhancing the perceived glossiness. Our data show that a retinal-image motion simulating motion parallax without head motion strengthened the perceived glossiness but that its effect was weaker than that of motion parallax with head motion. These results suggest the existence of an additional effect of the cross-modal coordination between vision and proprioception on glossiness perception. That is, motion parallax enhances the perception of glossiness, in addition to retinal-image motions of specular surfaces.